2018
DOI: 10.1016/j.jpsychores.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor DNA methylation and childhood trauma in chronic fatigue syndrome patients

Abstract: In conclusion, we replicated findings of NR3C1-1F DNA hypomethylation in CFS patients versus controls. Our results support the hypothesis of HPA axis dysregulation and enhanced GR sensitivity in CFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 60 publications
(81 reference statements)
1
25
0
Order By: Relevance
“…A total of 138 subjects (18.5%) had at least one type of CT (Table 3). This was similar to or lower than other general population samples (Brazil 17% [35]; China, no total, subscales 11, 7, 2, 2, 5, respectively [36]) and far lower than various patient groups and a homeless control sample [36][37][38]. CT and genetic liability were associated (χ 2 = 8.2, df = 2, p = 0.016).…”
Section: Resultssupporting
confidence: 65%
“…A total of 138 subjects (18.5%) had at least one type of CT (Table 3). This was similar to or lower than other general population samples (Brazil 17% [35]; China, no total, subscales 11, 7, 2, 2, 5, respectively [36]) and far lower than various patient groups and a homeless control sample [36][37][38]. CT and genetic liability were associated (χ 2 = 8.2, df = 2, p = 0.016).…”
Section: Resultssupporting
confidence: 65%
“…Another 2 gene-focused methylation studies, performed by Vangeel et al, 35,36 explored the DNA methylation status of the glucocorticoid receptor (GR) NR3C1 gene by using mass spectrometry (Sequenom EpiTYPER; Agena Bioscience, San Diego, California) in 76 patients with CFS and 19 healthy subjects in one study, and in 80 patients with CFS and 91 healthy control subjects in the other study. In both cases, the authors found hypomethylation at this locus in CFS participants in relation to control subjects.…”
Section: April 2019mentioning
confidence: 99%
“…There is also evidence of abnormalities in the epigenetic regulation of gene expression in CFS patients diagnosed via narrow criteria, most notably in gene promoter methylation patterns and elevation of microRNAs (miRNAs) involved in the regulation of the immune system (Brenu et al 2014a; de Vega et al 2014, 2017; Petty et al 2016; Vangeel et al 2015, 2018). The work of de Vega and others is of particular interest as these authors also selected patients according to criteria mandating the presence of post-exertional malaise and examined global patterns of gene methylation rather than a single gene as was the case for Vangeel and colleagues (de Vega et al 2014, 2017; Vangeel et al 2015, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The work of de Vega and others is of particular interest as these authors also selected patients according to criteria mandating the presence of post-exertional malaise and examined global patterns of gene methylation rather than a single gene as was the case for Vangeel and colleagues (de Vega et al 2014, 2017; Vangeel et al 2015, 2018). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation